Impact of telephone support programme using telemonitoring on stage of change towards healthy eating and active exercise in people with prediabetes. (June 2021) - Sakane, Naoki; Oshima, Yoshitake; Kotani, Kazuhiko; Suganuma, Akiko; Takahashi, Kaoru; Sato, Juichi; Suzuki, Sadao; Izumi, Kazuo; Kato, Masayuki; Noda, Mitsuhiko; Kuzuya, Hideshi
Introduction: This study evaluated the impact of a telephone support programme with telemonitoring on changes in healthy eating and active exercise in adults with prediabetes using the stage of change framework. Methods: We performed a post hoc analysis using data from the Japan Diabetes Outcome Trial-1. A total of 2607 participants aged 20–65 years with impaired fasting glucose were recruited from the workplace/community in Japan and randomized to a one year telephone support programme intervention arm ( n = 1240) or self-directed control arm ( n = 1367). Participants in both arms received monthly data feedback from a weight scale and pedometer. The main outcome measure was the stages of change toward healthy eating and active exercise. The secondary outcome was fasting plasma glucose (FPG). Results: After the one year intervention, the adjusted odds ratio of progressing to the action/maintenance stage in the intervention vs. control arm for healthy eating was 1.31 (95% confidence interval (CI) 1.21–1.43; p < 0.001), but that for active exercise was 1.07 (95% CI 0.99–1.15; p = 0.062). The intervention decreased FPG levels in participants in the contemplation stage, but not in the precontemplation, preparation and action/maintenance stages. Discussion: These findings suggest that the telephone support programme by healthcare providers advanced the stage of changes toward healthy eating in people with prediabetes. In particular, it decreased FPG levels in the contemplation stage.